Pengaruh Sensitivitas Suhu Dengan Metode Couple-Mode Terhadap Fiber Bragg Grating Fiber Optik - Nasrulloh Nasrulloh; Ary Syahriar; Rizki Noor Prasetyono (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2021)
The characteristics of  Fiber Bragg Grating (FBG) related to change of reflection power and wavelength shift in the fiber optic due to changes in temperature. Furthermore, the refractive index alo  affects the sensitivity of FBG. Using the Coupled-mode theory, the derivation of mathematical formula can be found to justify the effect of temperature in FBG. Also, the Coupled-mode theory is integrated numerically by the Transfer Matrix method to achieve the final equation of the effect of temperature in FBG. To obtain optimal results, several different parameter values are given to be analyzed. The results show that the temperatures are affecting the wavelength but have no effect on the peak of reflection power. In addition, by increasing the temperature and value of the refractive index will affect the enhancement of the sensitivity of FBG. These characteristics are a good opportunity to produce filters, sensors, or other applications by utilizing the characteristics of temperature in FBG.